Heating Plates Placement Structure for Optimal Muscle Stress Relief with Low Power Consumption - Mohamed Aminuddin, Mai Mariam; Abdul Rahim, Fatin Syafiqah (International Journal of Integrated Engineering, 2022)
A rapid contraction of the calf muscles, which can leave an hour of discomfort and soreness. Imagine that it happens to elderly people who live alone and bare their suffering helplessly. This research is therefore aimed at developing a device to automatically alleviate the pain of a cramp. This paper describes preliminary results in the development of an automatic cramp relief device focusing on how to minimize power consumption (heat plate structure design) but providing optimal performance to relax the stressed muscle. To suggest the structure, the TRIZ technique for solving problems is used. The suggested design was tested on 20 participants and the results revealed that the power consumption could be decreased by up to 66%, hence, enabling the future product to be able to use battery as a power source and operate for longer hours in single use of battery.